Peran Pengelolaan Hama Terpadu (PHT) dalam Pertanian Berkelanjutan Manfaat Ekonomi dan Kepatuhan Hukum - Haykal Yassin; Rian Aditia; Heni Alia Natasya (Journal of Science and Technology: Alpha, 2026)
Integrated Pest Management (IPM) represents a cornerstone of sustainable agriculture, combining ecological balance, economic efficiency, and legal compliance into a unified framework. This study explores the multifaceted role of IPM in promoting environmentally responsible farming practices while ensuring long-term productivity. By reducing dependence on synthetic pesticides, IPM mitigates soil and water contamination, preserves biodiversity, and supports climate resilience. Economically, IPM enhances farmers’ competitiveness by lowering input costs, stabilizing yields, and improving market access through compliance with safety standards. Legally, IPM aligns with national agricultural regulations and international conventions, reinforcing institutional accountability and farmer protection against sanctions. The integration of ecological, economic, and legal dimensions demonstrates that IPM is not merely a pest control strategy but a comprehensive system for advancing food security and sustainable development. The findings emphasize that IPM implementation strengthens agricultural innovation, supports educational objectives in Indonesia, and contributes to global sustainability agendas.